2012
DOI: 10.1364/oe.20.004085
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast nonlinear optical studies of silicon nanowaveguides

Abstract: Abstract:Results of a self-consistent ultrafast study of nonlinear optical properties of silicon nanowaveguides using heterodyne pump-probe technique are reported. The two-photon absorption coefficient and freecarrier absorption effective cross-section were determined to be 0.68cm/GW, and 1.9x10 −17 cm 2 , respectively and the Kerr coefficient and free-carrier-induced refractive index change 0.32x10 −13 cm 2 /W, and −5.5x10 −21 cm 3 , respectively. The effects of the proton bombardment on the linear loss and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
6
17
0
Order By: Relevance
“…The ultrafast response of waveguides has been studied previously in the context of adiabatic frequency conversion and ultrafast switching [26][27][28][29][30][31][32][33] . Collinear infrared pump-probe arrangements have been used to characterize pulse propagation and waveguide nonlinearities 34 .…”
mentioning
confidence: 99%
“…The ultrafast response of waveguides has been studied previously in the context of adiabatic frequency conversion and ultrafast switching [26][27][28][29][30][31][32][33] . Collinear infrared pump-probe arrangements have been used to characterize pulse propagation and waveguide nonlinearities 34 .…”
mentioning
confidence: 99%
“…In spite of its many advantages over other media, silicon-based all-optical signal processing inevitably suffers from nonlinear loss and patterning effects resulting from large TPA and free carrier absorption (FCA). The lifetime of free carriers generated by two-photon absorption is in the range of several hundred ps to several hundred ns [38] and slow carrier dynamics can limit the speed of signal processing. Several approaches have been proposed to mitigate the issue as shown in Figure 5-(b), (c), and (d).…”
Section: Crystalline Siliconmentioning
confidence: 99%
“…A comprehensive study of thermal drift in optical heterodyne systems can be found in [29]. These effects introduce instability into the signals of interest and specialized approaches utilizing radio receivers [18,30,31] or fast measurements with radio-frequency lock-in detection [19] have been employed to mitigate them. In this study, we introduce a heterodyning technique that detects two heterodyne signals; a technique thus requiring two lock-in detectors or a single lock-in detector with two phase sensitive channels (in this work we used a single Signal Recovery 7270 with dual-phase lock-in detection).…”
Section: Appendix: Two-frequency Heterodyning Techniquementioning
confidence: 99%